A case study of bowel prolapses after induced abortion - Agrawal, Neha; Malik, Neeru; Dabas, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Induced abortion, the intentional termination of pregnancy, is among the most common of gynaecological procedures. Depending on country-specific abortion laws, where abortion laws are highly restrictive, abortion is unsafe leading to maternal morbidity and mortality. This is a case study of unsafe abortion. In this case a 25-year-old G3P2L2 with previous 2 normal vaginal delivery had uterine perforation with bowel prolapse through the vagina following an dilatation and curettage of a missed abortion of 7 week and 6 days in a private hospital. Following the procedure patient had severe abdominal pain and bleeding from vagina, magnetic resonance imaging (MRI) was done. Patient came to our hospital with MRI. Patient was taken for exploratory laparotomy with uterine repair, bowel resection and anastomosis. Even though MTP Amendment act 2021 in India is liberal and government provides free contraception and abortion services by trained personnel, due to ignorance and misinformation, female often undergoes unsafe abortion. Unsafe abortion causes mild discomfort to grave injury like bowel prolapse leading to maternal death. Best preventive measure is awareness and easy accessibility.